Assess the Variables Impacting Elderly Individuals' Utilization of Primary Health Care Services at Makkah Healthcare Cluster 2024 - Amsha Ayied Alosimi,; Najla Dbyan Alshalaqi Alshammary,; Hala Eid Albakri,; Hanan Mohammed Banjar,; Hand Mohmmed Taher,; Nafah Diab Almatairy,; Njood Nader Al-Otaibi,; Salman Naif Aldalbhi,; Mohammed Abdallah Aldehaim,; Mohammed Aqoub Al-Otaibi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: In recent years, the proportion of older adults in emerging nations has dramatically increased.Makkah, as a religious and healthcare hub in Saudi Arabia, is home to a significant elderly population. The Kingdom of Saudi Arabia (KSA) has seen rapid demographic shifts in recent years, with a growing proportion of elderly individuals. This poses new challenges for the healthcare system, particularly in primary health care (PHC), which is the first point of contact for individuals in need of medical attention. The study aim: To investigate the Variables influencing the elderly population’s use of PHC services in the Makkah Healthcare Cluster (MHC)in the past 1, 3, and 6months. Method: A cross-sectional study design was used to collect data from 190 older adults in the MHC, KSA from January to July 2024. Results: Primary health care services were used by less than half of the participants in the past 1 month, by 68.4% in the past 3 months, and by 73.8% in the past 6 months. PHC services use was associated with age, education level, tobacco use, chronic illnesses, perceived general health status today, a physical component summary score, employment, and perceived general health status in the past 3 and 6 months. The primary predictor of PHC services use at 1, 3, and 6 months was chronic illnesses (OR = 13.32), (OR = 19.63), and (OR = 17.91), respectively. Conclusion: Although many factors were associated with PHC service utilization, the strongest predictor of PHC service utilization was chronic illnesses. This study recommended that develop more specialized services for elderly individuals within PHC centers, ensuring comprehensive care for chronic conditions and functional disabilities.